Characteristics of Chinese higher education EFL teachers' behaviors based on technological pedagogical content knowledge (TPACK) - Yang, Mingxing; Jeyaraj, Joanna Joseph; Ahmad, Norhakimah Khaiessa; Yang, Wei (Academy Publication, 2024)
Technological pedagogical content knowledge (TPACK) is pivotal for enhancing both learning and teaching processes, and it has garnered a share of scholarly attention in recent years, although few quantitative studies have been found on English as a foreign language (EFL) teachers of higher education in Guizhou, China. This study provides a comprehensive quantitative analysis of the integration of TPACK among EFL teachers in higher education in Guizhou province, China. A detailed EFL-TPACK framework coding protocol was employed to analyze the teaching videos of six EFL teachers with varying proficiency levels. These six teachers were selected from a survey that investigated 286 EFL teachers in higher education in Guizhou Province. The analysis categorized the teaching behaviors observed in the videos into seven distinct factors, meticulously quantifying the integration of technological (TK), pedagogical (PK), and content knowledge (CK), revealing significant disparities between the teachers. High-level teachers excelled in TPACK integration more than medium-level and low-level teachers, especially older ones. This study not only enables a deeper understanding of the practical application of TPACK in classroom settings but also emphasizes the dynamic nature of EFL-TPACK frameworks. The findings highlight the urgent need for targeted professional development strategies, including comprehensive technological training, a balanced emphasis on pedagogical and content knowledge, and the establishment of collaborative learning environments. These strategies are essential for enhancing TPACK integration skills across proficiency levels.